Application of modified adaptive bats sonar algorithm with doppler effect and levy flight (MABSA-DELF) to optimize mechanical engineering problems - Nur Naajihah, Ab Rahman; Nafrizuan, Mat Yahya; Mohd Haziq, Na'im Amin; Nur Iffah, Mohamed Azmi (Penerbit UMP, 2023)
This paper describes the application of the Modified Adaptive Bats Sonar Algorithm with Doppler Effect and Levy Flight (MABSA-DELF) to mechanical engineering design optimization issues. MABSA-DELF is a new algorithm that employs Doppler Effect and Levy Flight theory to improve the position of the transmitted bats’ beam. This project served as a showcase for the superior performance of MABSA-DELF. It was created using the MATLAB software’s computer simulation method. MABSA-DELF demonstrated a superior ability to solve engineering design problems in the fields of business, mechanical/manufacturing engineering, and electrical engineering. MABSA-DELF’s result are compared to those of other established algorithms.